Exploring the Effects of Tasks with Different Decision-Making Levels on Ball Control, Passing Performance, and External Load in Youth Football - Diogo Coutinho; Adam Leigh Kelly; Sara Santos; Pedro Figueiredo; David Pizarro; Bruno Travassos (MDPI AG, 2023)
This study aimed to understand how the design of decision-making tasks affects youth football players' ball control, passing performance, and external load. A total of 16 male youth football players (age: 12.94 ± 0.25 years) competed in various tasks based on the following levels of decision-making: (i) low decision-making (Low DM), which consisted of a predefined ball control and passing sequence; (ii) moderate decision-making (Mod DM), which consisted of maintaining possession in a square with four players and two balls while maintaining the same position; and (iii) high decision-making (High DM), which consisted of a 3 vs. 3 + 2 neutral players ball possession game. The study design consisted of a pre-post design (a 6 min pre-test game, a 6 min intervention, and a 6 min post-test game). The players' ball control and passing performance were measured using the game performance evaluation tool and notational analysis, while GPS data were used to determine their physical performance. The pre-post test analysis revealed decrements in players' ability to identify more offensive players after the Mod DM task (W = 9.50, p = 0.016), while there was an increase in their ability to receive the ball towards the space following the High DM task (t = −2.40, p = 0.016). Analysis between groups showed lower values in most ball control variables for the Low DM task compared to the Mod DM task (ball control execution, p = 0.030; appropriateness, p = 0.031; motor space, p = 0.025), while there were also lower values in the distance covered while sprinting (p = 0.042). Overall, prescriptive tasks (Low DM) that are repetitive in nature may affect players' perceptual attunement, whereas static tasks (e.g., Mod DM) may limit their ability to locate players in more offensive positions. Moreover, game-based situations (High DM) seem to acutely enhance players' performance, possibly due to contextual dependency. Overall, coaches should carefully consider the type of practice structure when designing tasks that aim to improve players' technical skills in youth football.